Interpretation as a Spiritual Practice: Buddhism and Cross-Cultural Hermeneutics - Beinorius, Audrius (Acta Orientalia Vilnensia, 2002)
The article deals with a problem of relation between textual interpretation and methodology of enlightenment in the Buddhist tradition. According to traditional exegesis, works of Buddhist philosophy are something like a samādhi, a sustained and penetrating contemplation of certain pathways of thought and insight. The author reveals that the Buddhist hermeneutical tradition is a tradition of realization, and devoid of any dichotomy between intellect and experience, the rational and the mystical. A principal role of the tradition is to supply the intertextual context of prejudices that makes the reading and talking possible and the background in which the revelation of meaning and the composition of a meaningful text become possible. Finally, it is pointed out that it is impossible to separate the study of Buddhist hermeneutics from the question of hermeneutics of the modern scholar who having his prejudices and preunderstandings determined by time and culture interpretes traditional Buddhist texts.